Identifying the indicators of premature starts in construction projects - Nur Fatin Izzati, Yusoff (2019)
This study discusses a factor of construction delay which is a premature start in construction projects. The study aims to identify the indicators of premature starts and determine the challenges associated with premature starts in construction projects. The method used to collect data for this study is done through an individual interview. The individual interview is performed with the industry practitioners that have experience in managing construction projects such as project managers and site engineers. This research involves construction and consultant companies that registered with the Construction Industry Development Board (CIDB), Grade 7. The data from the interview responses result will be analyzed using the thematic analysis. In qualitative research, one of the most common forms of analysis is thematic analysis. This method will examine, emphasize, pinpoint and record the pattern or themes within the data. By using this method, the pattern from the same data can be found and create new themes that represent the whole data. The finding shows that site, financial, and changes of activities and drawing are the top three indicators of premature starts in construction projects stated by the respondents, followed by the other indicators such as time, manpower, workplace issues, supplier and resources, and weather constraint. The other finding shows that people and financial are the top challenges associated with premature starts in construction projects stated by the respondents, followed by the other challenges such as drawing, materials and resources, supplier, weather, land acquisition, and fuel price. This study will provide information and knowledge to the project team about premature starts issue and guide the project team to be alert regarding this issue in construction industries. The project team should aware and take immediate actions to manage this issue so that the time, cost and quality of the construction projects will not be affected.